Relationship between endosperm proteins and quality in durum wheat (Triticum turgidum L. var. durum) - Carrillo J.M.; Martínez M.C.; Moita Brites C.; Nieto-Taladriz M.T.; Vázquez J.F. (Durum wheat improvement in the Mediterranean region: New challenges, 2000)
The influence of gliadins and glutenins, the seed endosperm proteins, on pasta cooking quality is analysed. In the high molecular glutenin (HMW) subunits, the negative effect of the HMW 20 is the most outstanding result. The gliadins gamma-42 and gamma-45 are markers of good and poor pasta quality, respectively. The low molecular weight (LMW) glutenin subunits are the most important prolamins influencing pasta quality. A rank of Glu-A3 and Glu-B3 alleles for several tests related to gluten strength is proposed.
Seminar on Durum Wheat Improvement in the Mediterranean Region: New Challenges, 2000/04/12-14, Zaragoza (Spain)